2021
DOI: 10.1186/s13075-021-02516-9
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory effects of human apatite crystals extracted from patients suffering from calcific tendinopathy

Abstract: Background Calcific tendonitis of the rotator cuff is due to carbonated apatite deposits in the shoulder tendons. During the evolution of the disease, an acute inflammatory episode may occur leading to the disappearance of the calcification. Although hydroxyapatite crystal-induced inflammation has been previously studied with synthetic crystals, no data are available with calcifications extracted from patients suffering from calcific tendinopathy. The objective of the study was to explore the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The present study revealed that the ExtraMito particles within mEPs are fundamental for inducing macrophage infiltration. Several proinflammatory cytokines, such as IL-1β, TNF-α, CXCL1 and IL-6, have been reported to initiate catabolic processes, especially in the early phase of tendinopathy 13 , 47 , 48 . We found that the mechanism underlying the loading-induced release of IL-6, CXCL1, and IL-18 was dependent on the degree of mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that the ExtraMito particles within mEPs are fundamental for inducing macrophage infiltration. Several proinflammatory cytokines, such as IL-1β, TNF-α, CXCL1 and IL-6, have been reported to initiate catabolic processes, especially in the early phase of tendinopathy 13 , 47 , 48 . We found that the mechanism underlying the loading-induced release of IL-6, CXCL1, and IL-18 was dependent on the degree of mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Calcific tendinitis is a cell-mediated disease passing through four stages of development, leading to fibrocartilaginous metaplasia and secondary mineralization which is subsequently resorbed in the resorptive phase by phagocytosis. [1] Crystal deposition incites an inflammatory response with increased tissue metabolism and activated inflammatory cells which are possibly responsible for the increased uptake of tracer on nuclear imaging. [8] A typical clinical picture is characterized by spontaneous onset, pain in the affected joint with referred pain, and spontaneous resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact etiology is not known, the development of calcium hydroxyapatite crystals deposition is believed to be due to tissue hypoxia, reduced oxygen tension resulting in cartilaginous metaplasia and secondary mineralization. [1] Characteristically affecting the rotator cuff tendons of the shoulder, it can be asymptomatic or symptomatic in patients and also has been noted at unusual sites such as the elbow, wrist, knee, and hip to name a few. [2] However, its imaging features may mimic a metastatic lesion and this case report highlights the dilemma that can face a clinician.…”
Section: Introductionmentioning
confidence: 99%
“…3 The development of calcium hydroxyapatite crystals deposition is thought to be due to decreased oxygen tension, leading to fibrocartilaginous metaplasia and secondary mineralisation. 4 Calcific tendinitis passes through four stages of evolution: (i) precalcific, asymptomatic phase, (ii) calcific or formative phase with varying symptoms, (iii) resorptive, most symptomatic phase due to extravasation of calcium hydroxyapatite into adjacent tissues, and (iv) post calcific phase associated with restriction of joint movements, tendinopathy and associated bursitis. 5 Though the shoulder joint is most frequent location of calcific tendinopathy, symptomatic calcific tendinitis at unusual sites (hip, knee, wrist and elbow) have been well described in literature.…”
Section: Introductionmentioning
confidence: 99%